Agriculture s shelf life - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Economics of Conservation Agriculture FAO, 2001. 74 pp. ISBN 9251046875. US$ 12 Euro 12.15